Educação sexual: estratégias metodológicas para o ensino médio - Aurino, Ana Débora Batista (2019)
Sexuality is an inherent phenomenon in the life of all people, because it is universal and, at the same time, unique to each individual. The construction of sexuality comes from its individual, social, psychic and cultural aspects. In adolescence, the morphological and physiological changes that occur to the body of young people favor the discovery of sexuality. Therefore, the importance of developing sexual education practices that allow dialogue, exchange experiences and information, as well as promote a greater autonomy regarding sexuality, and contribute to the health of adolescents. However, due to the lack of continuing education and teacher insecurity, this subject ends up being approached in a superficial way. Therefore, this research has as main objective, to propose methodological strategies, constructed from pedagogical experiences in the school space, to help teachers of basic education to work sex education in high school. Therefore, through a quanti-qualitative approach based on a participant research directed to two third year classes of a State secondary school in João Pessoa-PB, developed active methodological strategies of learning, focused on the ludic and student's protagonism. The answers obtained from the questionnaires and the observation of the actions developed were analyzed using a technique called content analysis. The subjects of the survey were 56 students, mostly girls, between 16-20 years of age. The students condom use is related to protection against pregnancy and/or diseases/infections, whereas non-use is related to the use of another contraceptive method or simply because they do not like to wear condoms. It was verified that the students easily understand of the contents of the anatomy of the human genital system, than human reproductive physiology. Through "Dynamics with Post it: Sex and Sexuality" it was observed that they did not show a clear understanding of what sex and sexuality was, presenting several mistaken ideas of what these concepts represent. Through the "Dynamic man/boy thing x woman/girl thing" and during the analysis of three songs it was noticed that the students have social representations of gender focused mainly on the corporal and behavioral aspects of each gender. Through the activity "Contraceptive methods and STI" developed in partnership with a health professional, it was possible to show the main STI and contraceptive methods used mainly by the adolescent public, besides teaching how to use correctly male condom, as a way of awareness of students who are at risk. Through the MEQ (Methodological Evaluation Questionnaire) it was possible to understand the reasons why students consider important to promote sex education activities in school, what they enjoyed and disliked about the activities developed in this work and what contents they would like to be addressed. Thus, this work can be used as a subsidy, helping other teachers to approach sexual education through the use of strategies in the form of a didactic sequence manual